1990
DOI: 10.1002/ptr.2650040407
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of thioacetamide‐induced hepatotoxicity by biflavanones of Garcinia kola

Abstract: Kolaviron, a mixture of Garcinia biflavonoids GB-1 (ll-3-I-4'-ll-4"-I-5-II-5-I-7-II-7-heptahydroxy-3,8"-biflavanone), GB-2 (1I-3-11-3'-1-4'-11-4"-1-5-11-5-1-7-1I-7-octahydroxy-3,8"-b~avanone) and kolaflavanone (11-3-11-3'-1I-4-I-5-11-5-1-7-11-7-heptahydro~-3,8-biflavanone) obtained from Garcinia kola, protected rats against the toxic effects of thioacetamide in uiuo. The biflavonoid mixture at a dose of 100mg/kg i.p. reduced the thiopental-induced sleep in thioacetamide-poisoned rats, both in the chronic and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…The animals in group 3 received curcumin (200 mg / kg /day) [18] in corn oil by gavage for the first 7 days followed by a daily administration of both curcumin and DBP concurrently for the last 9 days of the experiment. All the animals in group 4 received kolaviron (200 mg / kg /day) [9,19] dissolved in the vehicle and were also treated with DBP in the same manner as those of group 3. Twenty-four hours after the last treatment, all rats were sacrificed by cervical dislocation and blood was collected by cardiac puncture.…”
mentioning
confidence: 99%
“…The animals in group 3 received curcumin (200 mg / kg /day) [18] in corn oil by gavage for the first 7 days followed by a daily administration of both curcumin and DBP concurrently for the last 9 days of the experiment. All the animals in group 4 received kolaviron (200 mg / kg /day) [9,19] dissolved in the vehicle and were also treated with DBP in the same manner as those of group 3. Twenty-four hours after the last treatment, all rats were sacrificed by cervical dislocation and blood was collected by cardiac puncture.…”
mentioning
confidence: 99%
“…Removal of the solvent in vacuo in a rotary evaporator provided an organic extract (600g). Kolaviron was isolated according to Iwu et al 3 as modified by Farombi et al 4 Briefly, the powdered seeds were extracted with light petroleum ether (b.pt 40-60 o C) in a soxhlet for 24 h. The defatted, dried marc was repacked and extracted with acetone (Me 2 CO). The extract was concentrated and diluted twice its volume with water and extracted with ethyl acetate.…”
Section: Plant Material Preparation Of Extract Fractions and Compoundsmentioning
confidence: 99%
“…In vivo experiments presented biflavonoids as hepatoprotective, increased RNA synthesis in hepatocytes inhibited expression of EBV gene in addition to anti-spasmogenic activities and antibradykinin [13][14][15][16]. Recently, it was shown that biflavonoids are effective in the management of tuberculosis and postmenopausal breast cancer [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that biflavonoids are effective in the management of tuberculosis and postmenopausal breast cancer [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Two TLC chromatographic methods had been used to separate and determine biflavonoids and flavonoids from C. sempervirens L. [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation